Areas of Interest for the Incorporation of Gamification in Industrial Engineering: Analysis of three universities in Colombia - Valencia-Rodríguez, Orlando; Forero-Páez, Yesid; Pulgarín-Arias, Laura; Chica Otálvaro, Sarha Melissa; Pinzón-Salazar, Sebastián (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research determined critical areas of interest for the incorporation of playful activities in programs of industrial engineering in three Colombian universities, from the perception of students and teachers. The current nature of the participating programs and their curricula were evaluated, which allowed the identification of common themes among the educational institutions. A total of 125 surveys were applied, 109 to students (87.2%) and 16 to teachers (12.8%). Teachers consider topics in the area of Operations Research to be more complex, while for students it was mainly in Production topics. No significant correlations were found between the three universities.